Determinants of Customer Satisfaction and Customer Loyalty in Amhara Credit and Saving Institute (ACSI): The Case of Waghimera Zone Sekota Town - Gebremichael Getahun Amha (International Journal of Marketing & Human Resource Research, 2020)
The main objective of the study was to assess and analyze customer satisfaction and customer loyalty of ACSI in Sekota town. Accordingly, this study was used explanatory research design to examine the effect of independent variables on dependent variable. The study used mixed research approach. The study used both primary and secondary data type and sources. By using simple random sample technique total of 400 closed and open-ended self-administered questionnaires was distributed to the customers. The collected data was analyzed by descriptive and multiple regression analysis method by using SPSS version20. Overall findings from this study revealed the dimensions of service quality vary in the degree to which they drive customer satisfaction and customer loyalty. The results depicted that service quality; corporate image &Price were found to have positive and significant association with customer satisfaction & customer loyalty. The ACSI should continuously monitor the environment for changes with a motive of addressing the pricing policies of the rival FI and it should differentiate its service offerings in a way that could enable the ACSI to gain a competitive advantage. The ACSI is, thus, recommended to devise operations and marketing strategies that focus on the dominant service quality dimensions in order to enhance customer satisfaction and, in turn, foster positive customer loyalty.